Template complex synthesis of octadecan-1-amine with 2- benzoylpyridine and Cu2+: structural, anticancer, DPPH, SOD and FRAP studies - S. Vennila; K.S. Nagaraja; L. Lakshmi; V Radhakrishnan (Next Research, 2026)

Biodegradation of Polycyclic Aromatic Hydrocarbons by the Biofilm Forming Bacteria Priestia aryabhattai BMRS3B Isolated from the Rhizosphere of Oryza sativa - Ananthalekshmi L P; Soumya P; Radhakrishnan E K; Jayachandran K (Water, Air, & Soil Pollution, 2025)

Unveiling Hidden Water Resources: Deep Learning and Remote Sensing for Subsurface Hydrology for Environmental Health - Jampani Satish Babu; Dinesh G.; R. Suganya; P. Radhakrishnan; Anand Sutar; Alex David S.; L. Malleswara Rao (Remote Sensing in Earth Systems Sciences, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Fluorescent N-Doped Carbon Dots as a Biocompatible Sensor for Thiophanate-Methyl Detection - K. Radhakrishnan; R. Suriyaprakash; L. Srimathi Priya; P. Saravanan; Mir Waqas Alam; Pitcheri Rosaiah; Guru Prakash Nunna; Tae Jo Ko (Journal of Fluorescence, 2025)

Advancing nutraceuticals in a promising frontier in modern healthcare - Flora Shah; Karuppiah Nagaraj; S. Kamalesu; L. Radhakrishnan; Renuka Venkatachalapathy (Food and Humanity, 2024)

Innovative nanotechnological solutions for sustainable agriculture amidst rising population demands - Flora Shah; Karuppiah Nagaraj; Sanyukta Papriwal; Gargi Selwal; Ruchik Mistry; Prasenjit Maity; S. Kamalesu; L. Radhakrishnan; Renuka Venkatachalapathy (Food and Humanity, 2024)

Lyophilized rumen fluid as a ruminal fermentation modifier in high grain-fed acidotic goats - A. Ruba Nanthini; C. Valli; L. Radhakrishnan; D. Balasubramanyam; A. V. Mangalagowri (Tropical Animal Health and Production, 2024)

Effects of Zinc Oxide Nanoparticles Supplementation on Growth Performance, Meat Quality and Serum Biochemical Parameters in Broiler Chicks - V. Mozhiarasi; R. Karunakaran; P. Raja; L. Radhakrishnan (Biological Trace Element Research, 2024)

A critical review on pyrolysis method as sustainable conversion of waste plastics into fuels - K. Radhakrishnan; P. Senthil Kumar; Gayathri Rangasamy; L. Praveen Perumal; S. Sanaulla; S. Nilavendhan; V. Manivasagan; K. Saranya (Fuel, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Altered functional network connectivity and working memory dysfunction in adolescents with epilepsy - Jennifer Vannest; Rupa Radhakrishnan; Ana M. Gutierrez-Colina; Shari L. Wade; Thomas Maloney; Angela Combs; Luke Turnier; Shelby Merder; Mekibib Altaye; Tzipi-Horowitz-Kraus; Avani C. Modi (Brain Imaging and Behavior, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Hemodynamics mediated epigenetic regulators in the pathogenesis of vascular diseases - C. L. Karthika; S. Ahalya; N. Radhakrishnan; C. C. Kartha; S. Sumi (Molecular and Cellular Biochemistry, 2021)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Psidium guajava Leaf Extracts and Their Quercetin Protect HepG2 Cell Lines Against CCL4 Induced Cytotoxicity - K. Vijayakumar; R. L. Rengarajan; R. Radhakrishnan; Shilu Mathew; Ishtiaq Qadri; A. Vijaya Anand (Indian Journal of Clinical Biochemistry, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

New tetranorlabdanoic acid from aerial parts of Salvia aethiopis - Radhakrishnan Srivedavyasasri; Miriah B. White; Tatyana S. Kustova; Nadezhda G. Gemejiyeva; Charles L. Cantrell; Samir A. Ross (Natural Product Research, 2018)

Enhanced anti-fibrogenic effects of novel oridonin derivative CYD0692 in hepatic stellate cells - Fredrick J. Bohanon; Xiaofu Wang; Brittany M. Graham; Anesh Prasai; Sadhashiva J. Vasudevan; Chunyong Ding; Ye Ding; Geetha L. Radhakrishnan; Cristiana Rastellini; Jia Zhou; Ravi S. Radhakrishnan (Molecular and Cellular Biochemistry, 2015)

Anti-inflammatory activities of aqueous/ethanol and methanol extracts of Perna viridis Linn. in mice - K. L. Sreejamole; C. K. Radhakrishnan; J. Padikkala (Inflammopharmacology, 2011)

ttime: an R Package for Translating the Timing of Brain Development Across Mammalian Species - Radhakrishnan Nagarajan; Richard B. Darlington; Barbara L. Finlay; Barbara Clancy (Neuroinformatics, 2010)